2000
DOI: 10.1152/ajpendo.2000.279.6.e1335
|View full text |Cite
|
Sign up to set email alerts
|

Direct effects of growth hormone on production and secretion of apolipoprotein B from rat hepatocytes

Abstract: The aim of this study was to investigate the direct effects of growth hormone (GH) on production and secretion of apolipoprotein B (apoB)-containing lipoproteins from hepatocytes. Bovine GH (5-500 ng/ml) was given for 1 or 3 days to rat hepatocytes cultured on laminin-rich matrigel in serum-free medium. The effects of GH were compared with those of 3 nM insulin and 500 microM oleic acid. GH increased the editing of apoB mRNA, and the proportion of newly synthesized apoB-48 (of total apoB) in the cells and secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
41
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 51 publications
(89 reference statements)
4
41
0
Order By: Relevance
“…We have previously observed that GH incubation of hepatocytes using the same culture conditions as used in this study results in a 50% increase in triglyceride synthesis (28). Taken together, our results indicate that increased expression of SREBP-1c, FAS, or GPAT mRNA is not necessary for an effect of GH on triglyceride biosynthesis in vitro.…”
supporting
confidence: 76%
“…We have previously observed that GH incubation of hepatocytes using the same culture conditions as used in this study results in a 50% increase in triglyceride synthesis (28). Taken together, our results indicate that increased expression of SREBP-1c, FAS, or GPAT mRNA is not necessary for an effect of GH on triglyceride biosynthesis in vitro.…”
supporting
confidence: 76%
“…The secretion of apoB-48 and apoB-100 from primary mouse hepatocyte cultures was estimated by labeling the cells with a [ 35 S]methionine-cysteine mix (Amersham Biosciences) for 2 h followed by a 4 h chase in culture medium supplemented with 10 mM methionine, as described (38,43,44). Labeled apoB-48 and apoB-100 were isolated by immunoprecipitation with 10 Al of polyclonal rabbit anti-human apoB antibodies (DakoCytomation, Glostrup, Denmark), followed by 5% polyacrylamide gel electrophoresis containing SDS.…”
Section: Estimation Of Apob Secretionmentioning
confidence: 99%
“…Many factors have been reported to be able to regulate apoB mRNA editing in the rodent liver or hepatic cells. In addition to the developmental stage (15,39), interventions such as growth hormones, estrogen, thyroid hormones, insulin, fasting, carbohydrate refeeding, treatment with ethanol, modulation of calcium concentration, and phosphorylation status affect editing (8,9,12,14,27,30). However, the exact molecular mechanisms that regulate apoB mRNA editing activity remain largely unclear.…”
mentioning
confidence: 99%